Bacterial isolates from diabetic foot ulcers and their antimicrobial resistance profile from selected hospitals in Addis Ababa, Ethiopia - Atlaw, Asegdew; Kebede, Habtamu Biazin; Abdela, Abdurezak Ahmed; Woldeamanuel, Yimtubezinash (Frontiers in Endocrinology, 2022)
Introduction: Infected diabetic foot ulcer (IDFU) is a worldwide problem associated with diabetes mellitus. It could lead from soft tissue infection to bone infection and is a leading cause of lower limb amputation. Gram-negative and Gram-positive bacteria, including anaerobic bacteria and fungi, are considered potential causes of infection. The early diagnosis of DFU infection and appropriate treatment based on the identification of the pathogens and their antimicrobial susceptibility pattern is important for good prognosis. Therefore, the purpose of this study was to isolate the bacteria that infect foot ulcers in selected Hospitals and determine their antimicrobial resistance profile. Method: An institutional-based multicenter, cross-sectional study was conducted in selected Hospitals in Addis Ababa, Ethiopia, from November 2020 to May 2021. A sterile swab was used to collect samples from the foot ulcer and a sterile needle to collect pus. Isolates were identified by culture, Gram-staining, and a series of biochemical tests. For each bacterial species identified, the antibiotic profiling was determined by the Kirby-Bauer disk diffusion method. Results: one hundred and twenty-seven pathogenic bacteria were isolated from samples taken from 130 patients with a diabetic foot ulcer. Sixty-eight percent had growth of multiple microorganisms. Two-thirds (66.7%) of the isolates were gram-negative bacteria. The predominant bacterial species were S.aureus 25.19% (32/127), Pseudomonas species 18.89% (24/127), and Escherichia coli 16.53% (21/127). Overall, 92.9% (118/127) of the isolates were identified as multi-drug resistant. Gram-positive isolates were susceptible to chloramphenicol, clindamycin, and amikacin. Gram-negative isolates were also sensitive to chloramphenicol, aztreonam, and amikacin. Conclusion: The majority of bacteria isolated from patients presenting with Diabetic foot ulcer infections were found to be multi-drug resistant in the study sites of the current study. The results demonstrate the importance of timely identification of infection of diabetic foot ulcers, proper sample collection for identification of the pathogens, and for determining their antibiotic susceptibility pattern before initiating antimicrobial treatment